Acute stress blunts prediction error signals in the dorsal striatum during reinforcement learning - Carvalheiro, Joana (2021)
Acute stress is pervasive in everyday modern life and is thought to affect how people make choices and learn from them. Reinforcement learning, which implicates learning from the unexpected rewarding and punishing outcomes of our choices (i.e., prediction errors), is critical for adjusted behaviour and seems to be affected by acute stress. However, the neural mechanisms by which acute stress disrupts this type of learning are still poorly understood. Here, we investigate whether and how acute stress blunts neural signalling of prediction errors during reinforcement learning using model-based functional magnetic resonance imaging. Male participants completed a well-established reinforcement-learning task involving monetary gains and losses whilst under stress and control conditions. Acute stress impaired participants' (n = 23) behavioural performance towards obtaining monetary gains (p < 0.001), but not towards avoiding losses (p = 0.57). Importantly, acute stress blunted signalling of prediction errors during gain and loss trials in the dorsal striatum (p = 0.040) - with subsidiary analyses suggesting that acute stress preferentially blunted signalling of positive prediction errors. Our results thus reveal a neurocomputational mechanism by which acute stress may impair reward learning.